Who needs a world view? - Geuss, Raymond (Harvard University Press, 2020)
"Philosophers-professionals and the armchair variety-are given to defending comprehensive world views. Raymond Geuss, one of the most celebrated thinkers of our time, dispenses with this ambition for intellectual unity. Ranging across the history of art and ideas, Geuss argues for flexibility, doubt, and the accommodation of unresolved complexity"--